Population Structure and Polymorphism of Ceriodaphnia cornuta in Kotmale Reservoir - Chandrananda, W.P.N.; Piyasiri, S. (My University, 2013)
A study of zooplankton was carried out in Kotmale reservoir, from August 1990 to December 1991. Vertical and horizontal sampling was done once a month near the dam of the reservoir, between 1100 hours to 1200 hours. A closing type net with mesh size of 50p m was used for collection of zooplankton. Ceriodaphnia cornuta is a cosmopolitan species and the dominant form in the cladoceran community of Kotmale reservoir. It represented 98% of the whole population at certain months. Its population structure comprised nymphs and adults throughout the year. Ceriodaphnia cornuta showed polymorphism. Two morphological forms were identified. One form (horned form) had a comparatively smaller body (size range of 0.30-0.45 mm) with spines on the head region & the other (unhorned form) with a larger body (size range of 0.48-0.84 mm) without bearing spines. Abundance of morphological forms were different in 1990 and 1991. The spined form predominated in the epilimnetic waters where fish predation was high and the other form was found at all depths. Existence of such morphological forms may be an adaptation to minimize selective predation by fish.
Keywords: Population structure; Polymorphism Ceriodaphnia cornuta Kotmale reservoir